Programa Beca 18: Implementación de mecanismos de seguimiento y monitoreo a los becarios hasta su inserción laboral, y su aporte al desarrollo en la localidad de origen en la Universidad Católica San Pablo de Arequipa en el periodo 2019-2021 - Banich Galdos, Juan Carlos (2024)
Scholarship Program 18: Implementation of follow-up and monitoring mechanisms for scholarship recipients until their job placement, and their contribution to development in the town of origin at the San Pablo Catholic University of Arequipa in the period 2019-2021, is a research that seeks to examine if the services provided by the San Pablo Catholic University to the beneficiaries of the aforementioned scholarship are managing to contribute to the needs of the students, taking into account their characteristics, and above all, if they promote adequate follow-up and monitoring once the programs have ended. studies, both for their job placement, and with the impact they must generate for the development of their town of origin. Based on what has been described, this thesis aims to determine the factors that allow or prevent the Beca 18 program from generating adequate follow-up, monitoring and impact of the scholarship recipients during their studies and after them, by analyzing the relationship between the needs of the students and the services offered by the university, and highlighting the level of responsibility and commitment of the scholarship recipients, through respect for their customs and traditions. It also focuses on reviewing the work carried out by State agencies, through the PRONABEC program to articulate this between the private and public sectors. Likewise, it involves the participation and perception of Civil Society and Academia. Bringing together, in this way, the main social actors who must participate in the territorial development of a country. The research is carried out in the context of the proposal proposed by Sen (1996), indicating that capacity is important within social and political analysis, since for the individual to be able to live as he would like, it is strengthened by a policy. public, which is capable of transforming social environments. Likewise, as stated by Nussbaum (2012), when indicating that quality of life is subject to satisfying basic needs, and, furthermore, to the opportunity and capacity depending on the community. Asking the question: what is each person capable of doing and being? Since it indicates that this approach is related to respect for people's powers of self-definition and the importance of developing internal capabilities through education. The present study is qualitative and to carry it out it has used tools such as documentary review, the application of interviews and questionnaires. From the Social Management approach, this study allowed us to make decisions aligned with the search for development, well-being, good living and quality of life of the scholarship recipients who have accessed this opportunity and that allows them a true social transformation of themselves and of their town of origin. Likewise, it provides valuable information on the return on the State's investment in the applied source and in the formation of Human Capital in the rural locations from which the majority of the scholarship recipients come. As a general conclusion, it is highlighted that spaces of trust must be generated between the actors involved, given the level of articulation, through the participation and involvement that must be carried out between them. There must be support from parents and/or guardians, in addition to representatives of the scholarship recipient's home towns. And, it is very important, the degree of commitment and responsibility that the scholarship recipient must have, towards himself, on a personal and professional level, but without forgetting the contribution he must generate with his community. As a general recommendation, it is indicated that the program should start from respect and intercultural treatment, including the idiosyncrasies and customs in its various decentralized offices, to strengthen the link between scholarship recipients and the educational institution and thus generate interaction with other entities. It is considered that the contribution made by this research promoted improvements in monitoring, follow-up and contribution to development in the town of the scholarship recipients.